An experimental and modeling study of the enhancement of H2O2 on the activity of SNCR. (15th August 2022) - Wang, Fumei; Zhang, Rujie; Zeng, Yajun; Jia, Yujie; Shen, Boxiong; Yang, Jiancheng; Liu, Qinglong
Highlights: The effect of H2 O2 additive on SNCR De-NO activity was investigated. NO reduction was achieved from 0.3 s of SNCR to 0.015 s of H2 O2 -SNCR with Ɛ of 0.6 at 950 °C. The net reaction rate of H2 O2 -SNCR was about 57 times as fast as that of the conventional SNCR. The inhibition mechanism over 1000 °C and the promotion mechanism at 600–900 °C during H2 O2 -SNCR process were proposed. A updated kinetic model of H2 O2 -SNCR process was developed and verified. Abstract: An experimental and modeling study of the effect of H2 O2 on SNCR activity was investigated with the molar ratio of H2 O2 /NO (Ɛ) of 0.2–1.2. The results showed that the optimal temperature window was broadened from 950 to 1100 °C to 750–1100 °C with 37–89% NO reduction efficiency, and NO reduction was achieved from about 0.3 s of conventional SNCR to 0.015 s of H2 O2 -SNCR with Ɛ of 0.6 at 950 °C. The net reaction rate of H2 O2 -SNCR was about 57 times as fast as that of conventional SNCR. Furthermore, the promotion mechanism at low temperature (600–900 °C) and the inhibition mechanism at high temperature (over 1000 °C) in H2 O2 -SNCR process were proposed. The promotion mechanism can be explained by mainly increasing the production rate and concentration of NH2 and OH radicals owe to H2 O2 decomposition. It concluded that the production rate of NH2 increased by 120% with less residence time of 0.3 ms at 950 °C with Ɛ of 0.6, even the production rate and residence time of NH2 at 650 °C were both about an order of magnitude higher than those without H2 O2 at 950 °C. At high temperature, NO conversion decreased because of part NO formation potentially offsetting some of NO reduction via HNO + O2  ⇌ NO + HO2, HNO + OH ⇌ NO + H2 O, and NH + O2  ⇌ NO + OH. Finally, a updated kinetic model, involved 20 species and 112 elementary reactions, was developed and verified based on the detailed kinetics and experimental data, which well predicted the H2 O2 -SNCR process. This study aims to give a detailed insight into the enhanced H2 O2 -SNCR process for NO control.